Relationship between D-dimer and systemic embolism in patients with infective endocarditis - Ruken Bengi Bakal; Süleyman Karakoyun; Gökhan Kahveci; Olcay Özveren; Onur Omaygenç; Suzan Hatipoğlu Akpınar; Taylan Akgün; Nihal Özdemir (KARE Publishing, 2013)
Objectives: The aim of this study was to investigate the value of plasma D-dimer (DD) levels for predicting systemic embolism in patients with infective endocarditis (IE). Study design: A total of 42 patients (mean age: 46+-16 years; 78% males) with IE were included. Clinical, laboratory and echocardiographic findings of the patients were evaluated. Results: Increased plasma DD levels were determined in 13 patients with systemic embolism (p=0.016). Moreover, when patients were divided in two groups as DD >500 ng/dl and DD <500 ng/dl, systemic embolism was increased in the DD >500 ng/dl group (p=0.036). Receiver operating characteristics (ROC) curve analysis was performed to detect the best cut-off value of DD in the prediction of systemic embolism. DD >425 ng/dl yielded an area under the curve (AUC) value of 0.735 (95% CI 0.560-0.909, p=0.016). DD >425 ng/dl demonstrated a sensitivity of 77% and specificity of 62% for the prediction of clinical embolism. Hematocrit (r=-0.31, p=0.045), platelet count (r=-0.40, p=0.009), albumin (r=-0.37, p=0.026), and globulin (r=0.38, p=0.028) levels were correlated with DD levels. Conclusion: Plasma DD levels are increased in patients with IE who suffered from clinically significant systemic embolism. Further studies are needed to determine the predictive value of DD levels for clinically silent systemic embolism.